Act now: The effects of the 2008 Spanish disability reform - Matthew J. Hill; Jose Silva; Judit Vall (University of Kent, School of Economics, 2015)
We evaluate the effects of a reduction in the generosity of the Spanish disability system (DI) implemented in 2008. The reform reduced the benefits for individuals that have a short contributory history relative to their age, theoretically discouraging potential applicants to disability. However, due to the method used to calculate the extent of lost benefits, the reform actually introduced an incentive for individuals to apply for disability now. We use a life-cycle model with heterogeneous disabled workers to understand the potential impact of the reform and confirm the predictions of the model empirically. Our estimates show that the reform increased the probability of applying to DI by 33% for men. Consistent with the theoretical model, the effect is much stronger for individuals that lost their job in the previous period (83%).
Keywords: C33; I18; H51; 330; disability benefits; life-cycle model; policy evaluation